The richness of language is the richness of thought - Hasanzoda , Rukhshona; Khashimova , Sayyora (Journal of Pedagogical and Philological Research, 2026)
In recent years, English has become more than just a school subject in Uzbekistan; it’s become an important part of education. Speaking a foreign language offers numerous advantages, including access to top foreign universities, the international labor market, and modern technology. Knowing many languages ​​means having many keys to one lock.